Who Pays for Bank Insolvency? - Mayes, David G. 1946-2017; Liuksila, Aarno; Beck, Thorsten 1967-; Blowers, Bethany (Palgrave Macmillan UK, 2004)
How to avoid taxpayers paying for bank failures and banking crises? This book provides a proposal and a critique by twelve independent experts. It is addressed particularly to the threat posed in Europe by having large international banks, a history of bailouts and limited means of resolving any future banking crises. It shows how political imperatives and legal constraints currently result in economic losses in many countries round the world
Keywords: Finance; Banks and banking; Commercial law; Macroeconomics